2021
DOI: 10.3390/jpm11080814
|View full text |Cite
|
Sign up to set email alerts
|

Reduced MIP-1β as a Trait Marker and Reduced IL-7 and IL-12 as State Markers of Anorexia Nervosa

Abstract: Alterations in certain inflammatory markers have been found in individuals with anorexia nervosa (AN). However, their relation to clinical characteristics has not been extensively explored, nor is it clear whether they are trait or state features of the disorder. This cross-sectional study measured serum concentrations of 36 inflammatory markers in people with acute AN (n = 56), recovered AN (rec-AN; n = 24) and healthy controls (HC; n = 51). The relationship between body mass index (BMI), eating disorder psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 65 publications
0
15
1
Order By: Relevance
“…However, more recently, contradicting results in adults seem to question the narrative of uniform proinflammatory state in patients with AN: neither Caroleo et al ( 25 ) nor Nilsson et al ( 26 ), the latter being the largest study to date with 113 patients with AN and 114 HC, confirmed higher TNF-α, IL-1β or IL-6. Keeler et al in the most recent, very well-controlled study of 56 patients with AN and 51 HC, even found significantly lower levels of TNF-α and IL-6 in patients ( 27 ). Thus, the amount and even direction of proinflammatory cytokine changes in adult AN appear unclear.…”
Section: Introductionmentioning
confidence: 97%
“…However, more recently, contradicting results in adults seem to question the narrative of uniform proinflammatory state in patients with AN: neither Caroleo et al ( 25 ) nor Nilsson et al ( 26 ), the latter being the largest study to date with 113 patients with AN and 114 HC, confirmed higher TNF-α, IL-1β or IL-6. Keeler et al in the most recent, very well-controlled study of 56 patients with AN and 51 HC, even found significantly lower levels of TNF-α and IL-6 in patients ( 27 ). Thus, the amount and even direction of proinflammatory cytokine changes in adult AN appear unclear.…”
Section: Introductionmentioning
confidence: 97%
“…A recent study reported that IL-7 was related to musculoskeletal pain and impaired cognitive processing in patients with myalgic encephalomyelitis and chronic fatigue syndrome [ 49 ]. Some previous studies have related IL-7 to disturbed emotional function, e.g., depression [ 50 ] and anorexia nervosa [ 51 ]. In the present study, IL-7 was the protein with the highest discriminative power and was 66% higher in TMDM than CON.…”
Section: Discussionmentioning
confidence: 99%
“…Participants then completed a questionnaire pack, including questions on demographic characteristics, clinical characteristics for AN and recAN participants, and the EPIC-Norfolk FFQ. Partici-pants also completed questionnaires on mental health, data for which have been presented elsewhere [42] and will not be included in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…For the purpose of the current study, only data on IL-6, IL-10, and TNF-α were used as the DII has been previously validated against these inflammatory markers and they were available on the assay. For the results on group differences for the 36 inflammatory markers measured, see Keeler et al [42].…”
Section: Blood Sampling and Inflammatory Marker Quantificationmentioning
confidence: 99%
See 1 more Smart Citation